Appropriated literacies: The paradox of critical literacies, policies, and methodologies in a post-truth era - Bacon, Chris K. (Education Policy Analysis Archives, 2018)
Since 2016, there has been a proliferation of discourse around what has come to be called “post-truth.” Much of this discourse references critical literacies as a proposed means by which to disrupt post-truth across educational policy, pedagogy, and methodology. In this paper, I highlight the paradoxical degree of overlap between post-truth and the critical literacy approaches espoused to combat it. Left underexplored, these appropriated literacies may do more to embolden than to dismantle post-truth. I first typify three “first wave” responses to post-truth, exploring the affordances and limitations of each. I then provide recommendations for augmenting these responses through a renewed emphasis on power, domination, and liberation in critical literacies as a response to post-truth.